One Health: the need to move from theory to practice in a Public Health perspective (Epidemiology, Biostatistics, and Public Health, 2025)
The term One Health identifies a holistic vision that recognizes how human health, animal health and environmental health are closely interconnected and interdependent, to the extent that they influence and shape each other. Although this idea may seem banal and almost obvious, only in recent years have its prominence and scope significantly influenced the way we think about science, research, and the entire healthcare system, both locally and internationally.